Book Review: Under the Weather: Reimagining Mobility in the Climate Crisis. - Raymond Murphy (Critical Disaster Studies, 2023)
Under the Weather: Reimagining Mobility in the Climate Crisis is an insightful, important book that reports on a fine-grained investigation Sodero made of the consequences and response to the disasters resulting from Hurricane Juan in Nova Scotia in 2003 and Hurricane Igor in Newfoundland in 2010, with comparisons to Hurricane Sandy in New York, Hurricane Katrina in New Orleans, Hurricane Maria in Puerto Rico, the 1998 ice storm in northeastern North America and the Icelandic ash cloud. One original feature is the focus on mobility, how indispensable it is in modern societies, how it is disrupted by extreme weather, and the necessity of restoring and improving the mobility infrastructure in the context of climate change to make it more robust and resilient. Sodero traces how mobility is at the centre of disasters, in terms of disrupting the movement of humans and their mobility infrastructures, as well as in terms of nature’s “ecological mobilities”. Another original feature involves investigating fossil-fuelled mobility as the cause of these extreme weather disasters. Natural science demonstrated that contemporary climate change has human causes, and now its attribution studies are beginning to document that specific disasters are caused by climate change, but it hasn’t yet disaggregated overall gigatons of greenhouse-gas emissions into their causal sources, like driving and flying. Sodero argues that such fossil-fuelled mobility worsens severe weather and resulting disasters. This opens up neglected research into the demand for fossil-fuelled mobility as a cause of climate change.
Keywords: mobility; climate crisis; hurricane juan; nova scotia; hurricane igor; newfoundland; hurricane katrina; new orleans; hurricane maria; puerto rico; ice storm; iceland ash cloud; fossil fuels; infrastructure; climate routing; comparative disaster studies